Maternal intervention with a combination of galacto-oligosaccharides and hyocholic acids during late gestation and lactation increased the reproductive performance, colostrum composition, antioxidant and altered intestinal microflora in sows - Yu, Jian; Wang, Jie; Cao, Chang; Gong, Jiani; Cao, Jiaqi; Yin, Jie; Wu, Shusong; Huang, Peng; Tan, Bi’e; Fan, Zhiyong (Frontiers in Microbiology, 2024)
This study was conducted to evaluate the effects of dietary GOS and HCA during late gestation and lactation on reproductive performance, colostrum quality, antioxidant capacity and gut microbiota in multiparous sows. Methods: A total of 60 healthy multiparous cross-bred sows (Landrace × Yorkshire) were randomly fed 4 groups diets as follows: the basal diets (CTRL group), or the basal diets containing only 600 mg/kg GOS (GOS group), 600 mg/kg GOS + 100 mg/kg HCA (GOS + Low HCA group), and 600 mg/kg + 200 mg/kg HCA (GOS + High HCA group) from d 85 of gestation to weaning. Multiple parameters of sows were determined. There was a trend of shortening the labor process of sows (P=0.07) in the GOS group and GOS + Low/High HCA group. Compared with the CTRL group, the GOS + Low/High HCA group increased the average piglets weight at birth (P<0.05), and increased the IgA concentration of colostrum (P<0.05). In addition, serum triglyceride (TG) concentration was lower (P<0.05), and serum total antioxidant capacity (T-AOC) was higher (P<0.05) in the GOS and GOS + Low/High HCA groups than in the CTRL group at farrowing. Serum catalase(CAT) activities were higher in the GOS and GOS + High HCA groups than in the CTRL group at farrowing. The 16S rRNA analysis showed that GOS combination with high-dose HCA shaped the composition of gut microbiota in different reproductive stages (d 107 of gestation, G107; d 0 of lactation, L0; d 7 of lactation, L7). At the phylum level, the relative abundance of Bacteroidota and Desulfobacterota in G107, Bacteroidota, and Proteobacteria in L0, and Planctomycetota in L7 was increased in GOS + High HCA group (P<0.05). Spearman correlation analysis showed that Streptococcus was positively correlated with the serum TG but negatively correlated with the average piglets weight at birth (P<0.05). This investigation demonstrated that the administration of GOS in conjunction with HCA, to sows with nutrient restrictions during late gestation and lactation, further improved their antioxidant capacity and milk quality. The observed beneficial effects of GOS+HCA supplementation could potentially be linked to an improvement in gut microbiota disorders of the sows.